THE IMPACT OF INTERNATIONAL TRADE ON FOOD SECURITY: AN EMPIRICAL STUDY IN SOUTHEAST ASIA - Fitriadi, Agus; Markhamah, Siti (PUSAT KEWIRAUSAHAAN UNIVERSITAS BALIKPAPAN, 2024)
This study examines the intricate relationships between foreign direct investment (FDI), gross domestic product (GDP), imports, international trade, and food security in Southeast Asia. Utilizing panel data from 2002 to 2022, the research employs the Vector Error Correction Model (VECM) to analyze the dynamic interactions among these variables. The findings indicate that FDI significantly enhances both GDP and food security, highlighting its crucial role in the region's economic development. Conversely, while imports have a positive effect on GDP, GDP does not significantly influence import levels, suggesting that imports are more driven by external factors. Additionally, international trade positively affects imports but does not have a direct significant impact on food security. These results underscore the importance of fostering FDI and trade while also emphasizing the need for comprehensive policies that bolster domestic food production and economic diversification. The study concludes with recommendations for policy measures to create a more resilient and sustainable economic environment in Southeast Asia